Harald Cramér – A Great Statistician - Thorburn, Daniel (Lithuanian Journal of Statistics, 2013)
Harald Cramér is one of the great persons in the history of mathematical statistics and insurance mathematics in the twentieth century. He is perhaps the most well known Swedish statistician in modern time. The editor of “Lithuanian Journal of Statistics” has kindly asked me to write some notes on Harald Cramér, may be because my supervisor was one of Cramér’s pupils. I am not the best person to do so, but I will do my best. At the end I will also give some references for those who want to read more about Cramér.
Keywords: pedagogic performance; insurance mathematics; mathematical methods of statistics; administrative capacities and social skills